Naujausias intarpinių ir sta-kamienių veiksmažodžių sluoksnis: imitatyvai - Pakalniškienė, Dalia (Baltistica, 1996)
THE LATEST LAYER OF INFIX AND sta-STEM VERBS, I. E. IMITATIVES Infix and sta-stem verbs in the Lithuanian language have been shaping in several phases, they have passed a long way of formation beginning with the ancient Proto-Indo-European times until the innovations of the Lithuanian language. The latest layer of infix and sta-stem verbs are the imitatives with the cathegorically and lexically specified semantics as well as the phonetic and morphological peculiarities of the stem. Part of them have occurred as structural variants beside the causativa/resultativa or durativa/terminativa formations. That might have given an inspiration for the shaping of imitatives according to the emerged semantics, morphonological and morphological pattern.